INFLUENŢA FACTORILOR SOCIOCULTURALI ASUPRA FAMILIILOR MIXTE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2008)
At the present stage, the phenomenon of migration took such a scale that it threatens to transform the European countries into multi-ethnic societies. Ethnic mixed marriages raise a wide range of questions related to parents' cultural identities, being a meeting spot of two national cultures. Each ethnic community elaborates its own representations on how they should be and tends to keep this resulted image in the national conscience, to display it in traditions, actions and relations with the representatives of their own people. In our multi-ethnic society, marriages between representatives of different ethnic groups are a natural thing. Hence- forth, there results the necessity to learn about the psychological particularities of cohabitation, both as individual and social tasks